Preparation and characterisation of chemically deposited mixed (Bi1-x,Sb-x)(2)S-3 thin films - Patil, V. A.; Patil, A. R.; Choi, J. -W.; Palik, D. S.; Yoon, S. -J. (MANEY PUBLISHING, 2007)
Bismuth antimony sulphide (Bi1-x,Sb-x)(2)S-3 thin films have been deposited on glass substrates using arrested precipitation technique. Ingredients used for the deposition include triethanolamine complex of bismuth, aqueous thioacetamide and antimony trichloride. Stoichiometric mixtures of these ingredients are used for deposition of thin uniform and adhesive films on microslides. The preparative parameters such as temperature, pH, time, concentration of the reactants and substrate rotations are optimised to obtain good quality films. The morphology of as deposited films was examined by SEM and X-ray diffraction pattern. The optoelectronic properties of bismuth antimony chalcogenide thin films are strongly influenced by chemical composition of the films. Optical study shows that the films have an optical band gap of 2.3 eV for Sb2S3 and 1.8 eV for Bi2S3. Therefore, it is proposed to determine chemical composition of as deposited thin films by energy dispersive X-ray microanalysis and atomic absorption spectroscopy methods. The results obtained by these techniques show correct stoichiometry for all composition of the films grown by arrested precipitation technique. The purpose of the present paper is to study the preparative parameters, optical, electrical properties and morphology of bismuth antimony sulphide thin films. These films have W type conduction with high electric resistance. X-ray diffraction study shows that (Bi1-x,Sb-x)(2)S-3 is a ternary mixed chalcogenide, microcrystalline in nature. The growth mechanism, optical and structural properties of as deposited mixed metal chalcogenide thin films of (Bi1-x,Sb-x)(2)S-3 are discussed in the present paper.
Keywords: PRECIPITATION TECHNIQUE APT; OPTICAL-PROPERTIES; SB2S3